Observaciones recientes sobre las características del basamento económico del valle superior del magdalena en la región de payandé-rovira (tolima, colombia), y en especial sobre la estratigrafía y petrografía del miembro chicalá (=parte baja de la fm. sal (1984)
Field work carried out during the last six years led to significant advances on the knowledge of the economic-basement in the Upper Magdalena Valley, mainly on the one outcropping in the region between Payandé and Rovira (Dpt, Tolima), where upper most Lower Cretaceous sandstones ("Caballos Formation") lie unconformably on different levels of Triassic to Jurassic units (Payandé and Saldaña Formations). It seems clear that, after the accumulation of the Saldaña Formation and prior to the advance of the cretaceous sea, an important perior of faulting and erosion took place. This means that both Payandé and Saldaña Formations constitute the substratum for the cretaceous sedimentation and the served as temporary source rokcs during the early stages of the cretaceous transgression.One of the most interesting aspects, discovered in the last years, is that contrary to the situation known in other places of the Upper Magdalena Valley, in the Payandé-Rovira area the Saldaña Formation has a lower marine-fossiliferous portion, the Chicalá Member, which is constituted macroscopically by dark gray to greenisch siltstones, fine grained tuffaceous sandstones and some intercalated limestone-banks. However, microscopic analysis of  27 samples, taken along the whole section of the Chicalá Member, reveals that it is made of pyroclastites, hybrid sedimentites and bioclastic limestones. Toward the middle part, the Chicalá Member has yielded a fauna made of ammonites (Rhabdoceras sp. and others), bivalves and crinoids. The ammonites suggest a Rhaetian (Upper Triassic) age (Wiedmann and amp; Mojica 1980).  The upper part of the Saldaña formation, called Prado Member, consists mainly of variegated effusive and pyroclastic rocks, as well as some redbeds with sinsedimentary structures (desiccation cracks, raindrop impressions and vertebrate foot prints) indicating a subaerial, terrestrial environment.Up to now, the lower member is known only between the towns of Rovira and Payandé and has traditionally been considered to be a part of the Payandé Formation.  The upper member is present allover the region of the Upper Magdalena Valley and generally represents the Saldaña Formation. The exposures along the Chicalá creek (SW of Payandé) showed that the boundary between the Payandé Formation and the Chicalá Member is characterized by the ocurrence of thick bedded conglomerates and olistostromes composed entirely of limestone pebbles floating in a silty matrix. These conglomerates and olistostromes may be interpreted as the result of a strongs tectonic reactivation preceeding the Saldaña effusive events.  The Chicalá Member constitutes a local hybrid rock facies filling the shallow to very shallow platform occupied before by the Payandé Formation. Although the known Chicalá Member exposures are restricted to the Payandé-Rovira area, other occurrences may be expected at localities where the Payandé Formation is present.